EVOLUTION OF BREEDING RESEARCH IN BASMATI RICE (ORYZA SATIVA L.) IN PUNJAB, PAKISTAN - HASSAN , MIU; IRUM , A; ASHRAF , F; HASSAN , Z; WAQAR , M; PEERZADO , MB; USMAN , M; BILAL , H; SABIR , W; JAMIL , MW; JAVED , MI; TABBASSUM , MI; et al. (Biological and Clinical Sciences Research Journal, 2024)
Breeding research for Basmati rice commenced in 1926 when Rice Farm was established at Kala Shah Kaku in Punjab. 1933 Basmati-370, Mushkan-7, and Mushkan-41 were developed and released for commercial cultivation by the farming community. Despite the high aroma in grains, the Mushkan varieties faced challenges due to low yield potential and other quality issues, making them unsustainable for growers. Hybridization efforts began in 1933, resulting in the first cross of Basmati-370 with Palman-46, aimed at achieving high yield, earliness, and improved grain quality coupled with resistance to stem borers and rice blast. Basmati cultivation is predominant in the Kalar tract of Punjab. Two fine-grain varieties, C-622 and Basmati Pak, were introduced in 1960 through hybridization, with Basmati-Pak gaining popularity as Kernel Basmati. Ongoing research efforts focused on developing high-yielding varieties with enhanced quality. The approval of Basmat-385 in 1985, characterized by long grains measuring 6.6 mm in length and 1.6 mm in breadth, revolutionized Basmati rice production in Punjab. The globally renowned Super-Basmati variety received approval in 1996, featuring extra-long grains measuring 7.5 mm in length and 7.7 mm in breadth. After Super-Basmati, other prominent varieties like Basmati 2000, Basmati 515, PS-2, Kisan-Basmati, Punjab-Basmati, Chenab-Basmati, and Super Kainat-2000 were developed and periodically released for the farming community.